Computational Study of Spinodal Decomposition in Thin Layers - Rodin, Alexander (My University, 2022)
Phase separation through spinodal decomposition is the process where a mixture becomes unstable and spontaneously separates into two phases. The decomposition yields tortuous microstructures which are versatile in materials for transporting of liquids and molecules. In pharmaceutical industries, these types of materials are used in order to control drug releases from tablets and thus receive effective treatments against various diseases. A computational study is performed to improve the understanding of this decomposition in thin layers, by simulations of the conservative Allen-Cahn (AC) and Cahn-Hilliard (CH) equations. In an ongoing PhD project, at the department of Physics in collaboration with RISE Agrifood and Bioscience, the evolution in time of the decomposition is studied for mixtures of ethylcellulose (EC) and hydroxypropylcellulose (HPC) with ethanol as solvent, and generally, the phase separation occurs as the solvent evaporates. For both AC and CH, a pure diffusive model, and a model coupled with the Navier- Stokes equations (NS) for fluid flow are studied, where time-resolved results of length scales, curvatures, accuracy, etc., are compared with theory and the conducted experiments. The simulations could to some extent be compared to the experiments, and the AC models showed better agreement than the CH models. However, limitations in the models such as parameter settings is discussed. Further, insights for future work are proposed in order to compare the results properly. Comprising other models which appear to be accurate, and models that consider the effect of the evaporation.
Keywords: Spinodal decompostion, phase separation, Allen-Cahn, Cahn-Hilliard, modelling, simulation, drug release